Determination of Phosphodiesterase Type 5 Enzyme (PDE-5) Inhibitors and Analogues as Adulterants in Selected Herbal Products using Gas Chromatography–Electron Impact-Mass Spectrometer (GC-EI-MS) (Baghdad Science Journal, 2020)
Sildenafil, tadalafil, and vardenafil are phosphodiesterase type 5 enzyme (PDE-5) inhibitors used for the treatment of male erectile dysfunction. This present study aims to investigate 55 herbal products indicated for men’s sexual health from the Malaysian market for adulteration of PDE-5 inhibitors and analogues. The screening and identification of 20 PDE-5 inhibitors and analogues in herbal products of various forms (powder, capsules, tablets, and pastels) were conducted using gas chromatography–electron impact-mass spectrometer (GC-EI-MS). The analysis has shown that 19 herbal products were adulterated with PDE-5 inhibitors and analogues. Unique ion fragmentations and the presence of molecular ion serve as potential markers, and the limit of detection (LOD) was 0.1-5.0 µg/g. Ten PDE-5 inhibitors and analogues were randomly selected and successfully validated for simultaneous quantification, whereby the limit of quantitation (LOQ) was 5.0–50.0 µg/g with recoveries at 86.1-118.9%. The developed method of GC-EI-MS was shown to be simple, throughput, economical and had sufficient sensitivity to screen, identify and quantify PDE-5 inhibitors and analogues in herbal matrices.